(untitled) (INNOVATIVE ECONOMY, 2020)
Yahodzinska A.S. FOOD PRICE VOLATILITY IN UKRAINE Purpose. The aim of the article is to establish the level of food price volatility in Ukraine in order to develop national and regional food security programs in the framework of the 2030 sustainable development goals. Methodology of research. The theoretical basis of the study are the fundamental provisions of the food system, modern economic theory, which defines the goals and patterns of sustainable development of the world and Ukraine, scientific works of domestic and foreign scientists on food security, public administration and legislative settlement of this problem. The methodological basis of the study is the dialectical method and general and special methods of scientific knowledge. The following methods of economic research are used in the research process: abstract and logical (formation of principles, theoretical generalizations and conclusions); monographic (study of experience in food security); system analysis (determination of causal relationships); elementary-theoretical analysis and synthesis (establishment of patterns of development). Also in the process of research statistical methods are used: comparison, graphical and index. Using these methods, the state and dynamics of indicators of price fluctuations for food in Ukraine as a whole and in terms of territorial and administrative units, their economic and social consequences are analysed. The information base of the study is legislative and regulatory acts and program documents of state bodies of Ukraine and EU countries, official materials of the Cabinet of Ministers of Ukraine, methodical and statistical materials of the State Statistics Service of Ukraine and relevant services and institutions of other countries, scientific information from the world computer network Internet (research results of international organizations and FAO), the results of personal research of the author. Scientific work is based on the Agenda in the field of sustainable development "Ukraine 2016-2030". Findings. It is proved that if the established trends are maintained, it will not be possible to reach the target set in the National Report 2017 “Sustainable Development Goals: Ukraine” of CSW2 at consumer prices for food by 2030. In addition, the forecast values according to actual data significantly exceed the target. Originality. For the first time in Ukraine, the study is conducted on the basis of the indicators of the National Report 2017 "Sustainable Development Goals: Ukraine" in accordance with the identified objectives of CSW2, linking the results with the ability to achieve specific sustainable development goals – to reduce food price volatility. Practical value. Reducing food price volatility will have positive consequences for all actors in the food chain: consumers, producers and the state. Key words: volatility, index, price, food, Sustainable Development Goals, Ukraine.